A Review on Recent Orphan Drugs - Sharma, Anu; Saini, Priyanka; Chhimwal, Jyoti; Kabra, Mahaveer; Bhandari, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2013)
The drugs or biological products for the diagnosis, treatment, or, prevention of a rare disease or condition are orphan drugs. Even though the drugs intended to treat common disease where revenue is not expected by pharmaceutical manufacturer are as well categorized as orphan. United State of America (USA) was the first nation to propose a legal framework to encourage development and availability of orphan drugs. The orphan drug act was passed on January 28, 1983 by U.S.A.to stimulate the research, development, and approval of those products that treat orphan diseases. The regulation for orphan drugs varies in different countries. Orphan diseases are a spectrum of medical conditions with very different etiologies, the common denominator being the infrequency of their occurrence in the population. The new business model of orphan drugs could offer an integrated healthcare solution that enables pharmaceutical companies to develop newer areas of therapeutics, diagnosis, treatment, monitoring, and patient support. Incentives for drug development provided by governments, as well as support from the FDA and national organizations in special protocols are a further boost for the companies developing orphan drugs. Although there may still be challenges ahead for the pharmaceutical industry, orphan drugs seem to offer the key to recovery and stability within the market